Analisis Peran Dinas Pariwisata Kota dalam Pengembangan Wisata Lokal di Desa Sei Gohong - Yonatan Ari Santoso; Feny Delviani; Elia Wulandari; Riesmar Beladenta Gedalya (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study aims to describe the potential and uniqueness of Sei Gohong Tourism Village as a leading tourist destination in Palangka Raya City. Sei Gohong has a unique distinction compared to other tourist villages, namely, it bears both the names Sei Gohong Village and Sei Gohong Tourism Village, as reflected on the entrance gate sign. This dual identity makes Sei Gohong the only tourist village in Palangka Raya to achieve this designation earlier than other villages. Characteristically, Sei Gohong is better known as a water-based tourism destination, with only one land-based tourist attraction. In 2024, Sei Gohong Tourism Village achieved national recognition by being ranked among the top 50 Best Tourism Villages in the 2024 Indonesian Tourism Village Award, competing against more than 6,000 participants from across Indonesia. Currently trending tourist attractions include Danum Bahandang, formed from a former sand quarry and now a popular destination, and Kaja Bay, an orangutan sanctuary, accessible via a 30-minute journey. Visitors can interact directly with orangutans and feed them. Furthermore, the "Hai" (Big) House, the mascot and symbol of the origins of Sei Gohong Village, has been designated a cultural heritage site. The Sei Batu tourist attraction, managed by the Tourism Office, has experienced a decline in visitors due to changes in the natural rock formations and suboptimal management. Sei Gohong also offers educational tours in the form of guided forest walks to learn about local medicinal plants. This activity aligns with the livelihoods of the majority of residents, who rely on the sale of traditional herbal medicines, such as tree bark and roots. This research indicates that Sei Gohong Tourism Village has significant potential for sustainable education, but requires more structured management, particularly for underdeveloped tourist attractions.